The ghost next door [videorecording (DVD)] (Key DVD, 2005)
Hannah has noticed some odd goings-on in her neighborhood, especially since the new boy moved in next door. He is a strange one, pale as he is, and the family hasn't done much to the house yet. In fact, the whole place looks deserted!